The Impact of Blended Learning on Students’ Critical and Creative Thinking Skills in Science Learning: A Meta-Analysis - Nur Hikmah; Dhea Febriya; Hermalina Daulay; Akmam; Asrizal (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a meta-analysis to see the influence of Blended Learning in science learning on students' critical and creative thinking skills. The method used is meta-analysis with a population and research sample, namely scientific articles that have been published through Google Scholar on a national to international scale in 2016–2022, which discusses the application and influence of Blended Learning in science learning on students' critical and creative thinking skills. In the science subject category, which includes physics, biology, and chemistry. Blended learning influences in the highest category in its application in physics learning to students' critical and creative thinking skills. Whereas in chemistry lessons, has an effect on the medium category. Based on the level of education, blended learning has an influence on the high category when applied to the high school level. Meanwhile, if it is applied to the secondary school and university levels, blended learning only has an effect on the medium category. However, in general, the application of blended learning has a significant influence on students' critical and creative thinking skills. So, blended learning can be used as an innovation in science learning in an effort to improve students' critical and creative thinking skills.